Impact of Loan Deposit Ratio (LDR) on profitability: panel evidence from Commercial Banks in Malaysia - Rengasamy, Dhanuskodi (2014)
This paper examines the impact of Loan Deposit ratio on the profitability of Malaysian commercial banks for the period of 2009 to 2013. The study included all the eight locally owned commercial banks in Malaysia. Loan deposit ratio of the banks was the independent variable of the study. The dependent variable was profitability which measures through Return on Assets (ROA). Data were obtained from the annual reports of the banks. The ratio analysis along with descriptive, correlation analysis, paired T- test and regression analysis were used in this study. The result of the study indicated that there was a positive and nonsignificant impact of LDR on ROA is five banks (Bank 1, 2, 3, 4 and 8). Further the study revealed that only one bank (Bank 5) had a negative and non-significant impact of LDR on ROA and bank 7 had positive and significant impact.